EXAMINING THE TECHNOLOGY ACCEPTANCE MODEL IN THE ADOPTION OF NARCOTIC PRECURSOR REPORTING SYSTEM (SIPPRE) - Retno Agus Setiawan; Peppy Oktaviani (LPPM STMIK Pringsewu, 2021)
The use of Information and Communication Technology (ICT) among pharmacy professionals is increasing. Narcotic Precursor Reporting System (SIPPRE) is one of these technologies and can be used to supervise the distribution of narcotic precursors. The aim of this study is to investigate the predicting factors that influence the intention to use SIPPRE among pharmacy professionals. The Technology Acceptance Model (TAM) was used to shape the theoretical foundation for this study comprising perceived usefulness, perceived ease of use, attitude toward use, and intention to use. A quantitative approach was applied, using a five-point Likert scale questionnaire, adapted from previous studies. The participants for this study comprised 157 pharmacy professionals. The Results obtained using structural equation modeling indicated that pharmacy professionals perceived SIPPRE as an easy to use and useful system, and they favored its use in the future. In addition, perceived ease of use and usefulness significantly influenced attitudes toward the system. Apart from that, attitude toward use had a positive relationship with intention to use SIPPRE among pharmacy professionals. Surprisingly, perceived usefulness had a negative correlation with an intention to use. Overall, the TAM is a valid model to help explain pharmacy professional's intention to use SIPPRE. The results of this study provided useful insights for healthcare agencies to recognize the key elements that could improve the narcotic precursor reporting management.